Mechanism of Dihydromyricetin on Inflammatory Diseases - Sun, Yang; Liu, Shasha; Yang, Songwei; Chen, Chen; Yang, Yantao; Lin, Meiyu; Liu, Chao; Wang, Wenmao; Zhou, Xudong; Ai, Qidi; Wang, Wei; Chen, Naihong (Frontiers in Pharmacology, 2022)
Inflammation plays a crucial role in a variety of diseases, including diabetes, arthritis, asthma, Alzheimer’s disease (AD), acute cerebral stroke, cancer, hypertension, and myocardial ischemia. Therefore, we need to solve the problem urgently for the study of inflammation-related diseases. Dihydromyricetin (DHM) is a flavonoid mainly derived from Nekemias grossedentata (Hand.-Mazz.) J.Wen and Z.L.Nie (N.grossedentata). DHM possesses many pharmacological effects, including anti-inflammatory (NLRP-3, NF-κB, cytokines, and neuroinflammation), antioxidant, improving mitochondrial dysfunction, and regulating autophagy and so on. In this review, we consulted the studies in the recent 20 years and summarized the mechanism of DHM in inflammation-related diseases. In addition, we also introduced the source, chemical structure, chemical properties, and toxicity of DHM in this review. We aim to deepen our understanding of DHM on inflammation-related diseases, clarify the relevant molecular mechanisms, and find out the problems and solutions that need to be solved urgently. Providing new ideas for DHM drug research and development, as well as broaden the horizons of clinical treatment of inflammation-related diseases in this review. Moreover, the failure of clinical transformation of DHM poses a great challenge for DHM as an inflammation related disease.